Neuroprotective and antioxidant activities of bamboo salt soy sauce against H2O2-induced oxidative stress in rat cortical neurons - Noh, Min‑Young (2016)
Bamboo salt (BS) and soy sauce (SS) are traditional foods in Asia, which contain antioxidants that have cytoprotective effects on the body. The majority of SS products contain high levels of common salt, consumption of which has been associated with numerous detrimental effects on the body. However, BS may be considered a healthier substitute to common salt. The present study hypothesized that SS made from BS, known as bamboo salt soy sauce (BSSS), may possess enhanced cytoprotective properties; this was evaluated using a hydrogen peroxide (H2O2)‑induced neuronal cell death rat model. Rat neuronal cells were pretreated with various concentrations (0.001, 0.01, 0.1, 1 and 10%) of BSSS, traditional soy sauce (TRSS) and brewed soy sauce (BRSS), and were subsequently exposed to H2O2 (100 µM). The viability of neuronal cells, and the occurrence of DNA fragmentation, was subsequently examined. Pretreatment of neuronal cells with TRSS and BRSS reduced cell viability in a concentration‑dependent manner, whereas neuronal cells pretreated with BSSS exhibited increased cell viability, as compared with non‑treated neuronal cells. Furthermore, neuronal cells pretreated with 0.01% BSSS exhibited the greatest increase in viability. Exposure of neuronal cells to H2O2 significantly increased the levels of reactive oxygen species (ROS), B‑cell lymphoma 2‑associated X protein, poly (ADP‑ribose), cleaved poly (ADP‑ribose) polymerase, cytochrome c, apoptosis‑inducing factor, cleaved caspase‑9 and cleaved caspase‑3, in all cases. Pretreatment of neuronal cells with BSSS significantly reduced the levels of ROS generated by H2O2, and increased the levels of phosphorylated AKT and phosphorylated glycogen synthase kinase‑3β. Furthermore, the observed effects of BSSS could be blocked by administration of 10 µM LY294002, a phosphatidylinositol 3‑kinase inhibitor. The results of the present study suggested that BSSS may exert positive neuroprotective effects against H2O2‑induced cell death by reducing oxidative stress, enhancing survival signaling, and inhibiting death signals.